KEPEMIMPINAN TRANSFORMASIONAL DAN PERILAKUKEWARGAAN ORGANISASI KARYAWAN GENERASI MILENIAL - Nicholas Simarmata (Departemen Psikologi, Universitas Negeri Padang, 2025)
Organizations frequently engage in innovation and transformation initiatives to ensure their sustainability and facilitate progress in the face of complex and uncertain dynamic changes. This is often achieved by fostering organizational citizenship behavior (OCB) among employees, encouraging them to contribute beyond their formal job responsibilities. The millennial generation, which currently constitutes a significant portion of the workforce, encounters difficulties in fulfilling market demands and tends to demonstrate lower levels of OCB, influenced by various psychological and economic factors. Transformational leadership is recognized as a pivotal factor in facilitating the emergence and enhancement of organizational citizenship behavior (OCB). This research adopts a quantitative correlational design, utilizing standardized instruments to measure transformational leadership and OCB, both operationalized through a five-point Likert scale with cumulative scoring. The study sample includes 135 millennial employees from Company X in Bali, encompassing functional departments such as marketing, finance, human resources, and public relations. Participants were selected using a disproportional stratified random sampling method, with eligibility criteria requiring a minimum of one year of employment and at least a senior high school level of education, regardless of gender. Data were analyzed using Spearman’s rank-order correlation. The results indicate a statistically significant relationship between transformational leadership and OCB among the millennial workforce at Company X, evidenced by a p- value below 0.05 and a correlation coefficient of 0.298.